400 AU/mL IgG protective threshold against SARS-CoV-2 XBB reinfection in Chinese inactivated vaccine recipients: implications for booster vaccination - Yin, Zhiying; Yin, Mengcheng; Zhao, Fei; Fu, Canya; Xu, Wenjie; Fang, Quanjun; Gong, Xiaoying; Wang, Shuangqing; Zheng, Canjie (Frontiers in Immunology, 2026)
BackgroundData on antibody dynamics and protective threshold generated by infection with Omicron subvariants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), particularly among populations that have primarily (>90%) received inactivated coronavirus disease 2019 (COVID-19) vaccines, remain limited. Using data from two large-scale paired serosurveys, we analyzed real-world changes in SARS-CoV-2 antibody levels associated with specific hybrid immunity.MethodsThe history of COVID-19 vaccination and SARS-CoV-2 infection were recorded for each participant. Serum samples collected at three-month intervals were analyzed for antibody levels against nucleocapsid (N) and spike (S) proteins using chemiluminescent microparticle immunoassay (CMIA). Linear mixed-effects model (LMM) and restricted cubic spline analysis were applied to assess antibody dynamics and determine protection thresholds, respectively.ResultsA total of 4,065 participants were recruited in February and May 2023, with 2,894 completing both sampling rounds. Over three months, median IgG antibody levels declined by 28% (from 396.39 to 285.80 AU/mL). Prior infection and vaccination were significantly associated with higher antibody levels, while increasing age correlated with an annual decay of 0.38 AU/mL (most prominent in adults ≥60 years, 32.7% of whom fell below the protective threshold by follow-up). The IgG threshold for protection against XBB reinfection was 400 AU/mL, and each additional vaccination reduced reinfection risk by 13–15%.ConclusionThe 400 AU/mL IgG threshold provides a actionable quantitative guideline for prioritizing booster doses in Chinese adults aged ≥60 years (the fastest antibody decay subgroup) and high-risk groups. Routine antibody testing combined with this threshold could optimize targeted COVID-19 vaccination strategies in inactivated vaccine-predominant populations.